Diversity and Distribution of Fungi Associated with "Ikwe Pond" Water Source: Their Impact on Water Quality and Human Health - Mbong, Emem; Edem, Ekom; Hussain, Sajjad; Ntekpe, Mfon (International Journal of Environmental Sciences, 2023)
Purpose: Fungal infections are becoming more and more important because of increasing numbers of immunosuppressed patients. Nonetheless, waterborne fungi are associated with variety of health related conditions. Fungi in the aquatic ecosystem perform essential functions in biogeochemical cycles. However, knowledge of fungal communities associated to a particular aquatic ecosystem is important. In the present study, we seek to investigate the fungal distribution and diversity in Ikwe Pond, located in Eket. Methodology: A total of thirty different water points were sampled using 30 thoroughly washed 0.50L sterile plastic containers and cultured on SDA plates with 1ml of dilution factors 10-3 and 10-6 used as inoculums. Six fungal species namely Candida tropicalis, Aspergillus niger. Cryptococcus sp, Absidia sp, Geotricium sp, were isolated from the 30 sampling points. Findings: Upstream recorded a total of 27 spores, midstream had 14 spores while downstream recorded 8 spores. Also the colony count revealed that upstream had the highest number of fungal spores count. Clearly, the upstream (59.3%) and the midstream (78.6%) sampling points were dominated by Aspergillus niger while the downstream water column was dominated by Candida tropicalis (50%). Unique Contribution to Theory, Practice and Policy: In many countries, there has been little focus on the occurrence of fungi in water which can lead to severe health related issues but with monitoring on the frequency and distribution of fungi in our waters, this perceived health related complications can be checked.